POLITIK DAKWAH DAN DAKWAH POLITIK DI ERA REFORMASI INDONESIA - Rosa, Andi (WALISONGO, 2014)
This research activity parse Dzikir majlis Susilo Bambang Yudhoyono (SBY)"Nurussalam" which has a strategic role in the democratic era. His status as asociety organizations (NGOs) are positioned optimally by interest groups, politicalorganizations and even into the container. By analyzing the dataobtained throughinterviews and documentation, the results of this study indicate that this councilmakes verses of the Qurâan that deals with the concept of al-âummah, alukhuwwahal-islamiyya, and al-taÄwun as a cornerstone in interpreting paragraphintegrative social which is then used as a propaganda entity. Proselytizingas mass communication, political communication line with more likely to usecommunication as a way to mobilize the masses massif. Even activities have beenable to carry out the functions of political propaganda as part of the interest-groupsystem.***Penelitian ini berusaha untuk mengurai kegiatan Majelis Dzikir Susilo BambangYudhoyono (SBY) âNurussalamâ yang memiliki peran strategis di era reformasi.Statusnya sebagai organisasi masyarakat (Ormas) diposisikan secara maksimaloleh kelompok kepentingan, bahkan menjadi wadah lembaga politik. Denganmengganalisis data yang diperoleh melalui wawancara dan dokumentasi, hasilpenelitian ini menunjukkan bahwa majlis ini menjadikan ayat al-Qurâan yangberkaitan dengan konsep al-âummah, al-ukhuwwah al-islÄmiyyah, dan al-taâÄwunsebagai landasan dalam menafsirkan ayat sosial integratif yang kemudiandijadikan sebagai sebuah entitas dakwah. Dakwah sebagai komunikasi massa,sejalan dengan komunikasi politik yang lebih cenderung memanfaatkankomunikasi sebagai cara massif untuk menggalang massa. Bahkan kegiatannyatelah mampu melaksanakan fungsi politik dakwah sebagai bagian dari sisteminterest-group.Keywords: tafsir integratif, kampanye politik, majelis dzikir, interestgroup